Metaphor in second language academic writing. Issue 3 (17th July 2020) - Saneie Moghadam, Maryam; Ghafar Samar, Reza
Abstract: This study describes the quantitative aspects of metaphor in academic publications. In particular, we analyze the frequency of metaphor types and source domains in medical papers written by native and non-native speakers of English. The data have been collected from selected published articles on cancer and tissue engineering. The method combines a manual procedure with a semantic tagger and keyness statistics in Wmatrix software for metaphor identification. The results show that while the distribution of metaphor is relatively stable across tissue engineering and cancer articles written by native and non-native speakers, indirect metaphor is more often used than other types of metaphor. Moreover, the findings indicate that some metaphorical source domains are specifically used for a particular topic and that some are more frequently exploited by native speakers of English than by non-native speakers. This study has implications for English for Academic Purposes (EAP) pedagogy and the development of metaphorical awareness activities as it may set the ground for future corpus studies that analyze metaphor properties in academic registers.